2016
DOI: 10.1017/s1368980016000859
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and geographic food access and food security status among households with children

Abstract: Objective To examine the association of both perceived and geographic neighborhood food access with food security status among households with children. Design This was a cross-sectional study in which participants’ perceptions of neighborhood food access were assessed by a standard survey instrument, and geographic food access was evaluated by distance to the nearest supermarket. Multinomial logistic regression models were used to examine the associations. Subjects The Midlands Family Study included 544 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
1
36
0
2
Order By: Relevance
“…One potential interpretation of this finding is that participants perceiving lack of access as a significant problem are expressing barriers constraining their food shopping-related choices, such as the foods purchased, frequency of shopping trips, and transportation to stores. We have previously shown that residents’ perceptions of relatively lower availability of healthful foods and relatively greater lack of access are not particularly correlated with spatial availability measures of the built food environment but are strongly associated with household socioeconomic characteristics, including food insecurity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One potential interpretation of this finding is that participants perceiving lack of access as a significant problem are expressing barriers constraining their food shopping-related choices, such as the foods purchased, frequency of shopping trips, and transportation to stores. We have previously shown that residents’ perceptions of relatively lower availability of healthful foods and relatively greater lack of access are not particularly correlated with spatial availability measures of the built food environment but are strongly associated with household socioeconomic characteristics, including food insecurity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood food environments are commonly measured by “objective” measures such as geographic information system (GIS)-based measurements and store audits, but accounting for perceptions (e.g., perceived availability and accessibility of food or food stores measures) is arguably more important [ 17 ]. Though policies attempting to promote healthy eating have mainly focused on improving geographic proximity to the locations of healthy food outlets, the importance of using self-reported individual perceptions of the neighborhood food environment has been demonstrated [ 18 , 19 , 20 ]. Perceived accessibility to different food outlets may reflect individuals’ shopping behaviors, dietary behaviors, and nutritional status as well or better than objective measures of proximity [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, children experiencing different degrees of food insecurity had higher tendency to purchase foods from stores that contain less-healthful foods particularly the convenience ones, and also making unfavorable food choices such as purchasing unhealthy snack foods and sugar sweetened beverages (25,26). Although food literacy as a key component of shaping eating behaviors can improve food choices by helping food insecure children to develop their skills, many unmodi able factors contribute to make poor food choices such as household income level, poor food access and availability and the high prices of healthy food.…”
Section: Discussionmentioning
confidence: 99%